The financial and clinical implications of adult malaria diagnosis using microscopy in Kenya. - Zurovac, D; Larson, B; Akhwale, W; Snow, R (2006)
OBJECTIVE: A recent observational study undertaken at 17 health facilities with microscopy in Kenya revealed that potential benefits of malaria microscopy are not realized because of irrational clinical practices and the low accuracy of routine microscopy. Using these data, we modelled financial and clinical implications of revised clinical practices and improved accuracy of malaria microscopy among adult outpatients under the artemether-lumefantrine (AL) treatment policy for uncomplicated malaria in Kenya. METHODS: The cost of AL, antibiotics and malaria microscopy and the expected number of malaria diagnosis errors were estimated per 1,000 adult outpatients presenting at a facility with microscopy under three scenarios: (1) current clinical practice and accuracy of microscopy (option A), (2) revised clinical practice with current accuracy of microscopy (option B) and (3) revised clinical practice with improved accuracy of microscopy (option C). Revised clinical practice was defined as performing a blood slide for all febrile adults and prescribing antimalarial treatment only for positive results. Improved accuracy of routine microscopy was defined as 90% sensitivity and specificity. In the sensitivity analysis, the implications of changes in the cost of drugs and malaria microscopy and changes in background malaria prevalence were examined for each option. RESULTS: The costs of AL, antibiotics and malaria microscopy decreased from 2,154 dollars under option A to 1,254 dollars under option B and 892 dollars under option C. Of the cost savings from option C, 72% was from changes in clinical practice, while 28% was from improvements in the accuracy of microscopy. Compared with 638 malaria overdiagnosis errors per 1,000 adults under option A, 375 and 548 fewer overdiagnosis errors were estimated, respectively, under options B and C. At the same time, the number of missed malaria diagnoses remained generally low under all options. Sensitivity analysis showed that both options B and C are robust to a wide range of assumptions on the costs of drugs, costs of blood slides and malaria prevalence. CONCLUSIONS: Even with the imperfect microscopy conditions at Kenyan facilities, implementation of revised clinical practice (option B) would substantially reduce the costs and errors from malaria overdiagnosis. Additional interventions to improve the accuracy of microscopy (option C) can achieve further benefits; however, improved microscopy in the absence of revised clinical practice is unlikely to generate significant cost savings. Revision of guidelines to state explicitly age-specific indications for the use and interpretation of malaria microscopy is urgently needed. Further prospective studies are required to evaluate the effectiveness and costs of interventions to improve clinical practice and the accuracy of malaria microscopy.